2019
DOI: 10.1371/journal.pone.0217405
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lung recruitment maneuvers on post-operative pulmonary complications for patients undergoing general anesthesia: A meta-analysis

Abstract: Background Respiratory function would be impaired during general anesthesia period. Researchers devoted their energies to finding effective strategies for protecting respiratory function. Low tidal volume, positive end-expiratory pressure (PEEP), and lung recruitment maneuvers (LRMs) were recommended for patients under mechanical ventilation. However, based on the current evidence, there was no consensus on whether LRMs should be routinely used for anesthetized patients with healthy lungs, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 35 publications
3
38
1
Order By: Relevance
“…19 Meanwhile, a recent meta-analysis reported that ARM combining with LPV reduced the occurrence of PPCs and improved oxygenation in non-obese patients. 8 Although they did not conclude the ideal strategy as the variable techniques of ARM, they suggested that sustained inflation might be better than step-wise recruitment on the development of PPC. 8 We applied ARM immediately before and after pneumoperitoneum based on previous studies.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…19 Meanwhile, a recent meta-analysis reported that ARM combining with LPV reduced the occurrence of PPCs and improved oxygenation in non-obese patients. 8 Although they did not conclude the ideal strategy as the variable techniques of ARM, they suggested that sustained inflation might be better than step-wise recruitment on the development of PPC. 8 We applied ARM immediately before and after pneumoperitoneum based on previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…8 Although they did not conclude the ideal strategy as the variable techniques of ARM, they suggested that sustained inflation might be better than step-wise recruitment on the development of PPC. 8 We applied ARM immediately before and after pneumoperitoneum based on previous studies. 20,21 A previous clinical study that examined the effect of preemptive ARM only before pneumoperitoneum reported that preemptive ARM improved arterial oxygenation and AaDO 2 during the laparoscopic hysterectomy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Combining with PEEP, there was no remarkable reduction in the incidence of PPC. [ 13 ] Alveolar recruitment is achieved broadly by two types – sustained inflation of the lungs for 5–30 sec to a predetermined peak inspiratory pressure of 30–40 cm of H 2 O or incrementally increasing PEEP in a stepwise manner. [ 14 ] In the meta-analysis, it was found that sustained inflation technique may be better than stepwise lung recruitment maneuver in preventing PPC.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory function is impaired during general anesthesia [1]. Respiratory complications are associated with longer hospitalization and increased nancial cost [2].…”
Section: Introductionmentioning
confidence: 99%